Silver pyridine-2-sulfonate complex - its characterization, DNA binding, topoisomerase I inhibition, antimicrobial and anticancer response - Rendošová, Michaela; Vargová, Zuzana; Sabolová, Danica; Imrichová, Natália; Hudecová, Daniela; Gyepes, Róbert; Lakatoš, Boris; Elefantová, Katarína (Journal of inorganic biochemistry, 2018)
In the current study the ability of silver pyridine-2-sulfonate complex to exert multiple biological activities is compared with the pharmacological action of silver sulfadiazine (AgSD). Polymeric form of {[Ag(py-2-SO3)]}n (AgPS) was synthesized and characterized by analytical techniques (IR, CHN, TG/DTA, MS) and its molecular formula was established. The crystal structure was determined by X-ray diffraction method and the polymeric complex crystallizes in the triclinic P-1 space group. The stability of Ag(I) complex was verified by 1H and 13C NMR measurements and the interaction with calf thymus DNA through UV-VIS and fluorescence quenching experiments was studied. The Ag(I) complex was able to interact with DNA by dual binding mode: partial intercalation along groove binding. The binding constants were calculated to be in the order of 103 M-1. Topoisomerase I inhibition study have shown that silver complex is inhibiting its activity at concentration of 30 μM. The cytotoxic activity of AgPS and AgSD against mouse leukaemia L1210 S, R and T cell line was also evaluated. AgPS showed higher cytotoxicity than AgSD after 48 h incubation. The results suggest that mechanism of cell death is necrosis with a contribution of late apoptosis. Antimicrobial testing indicates higher growth inhibition effect of AgPS with comparison to commercially available AgSD.
Keywords: Topoisomerase I Inhibitors; Anticancer; Antimicrobial; nádorové buněčné linie; apoptóza; Anti-Bacterial Agents; Coordination Complexes; Bacteria; inhibitory topoisomerasy I; komplexní sloučeniny; Pyridines; pyridiny; stříbro; Silver; Mice; Cell Line, Tumor; Microbial Sensitivity Tests; Silver sulfadiazine; Topoisomerase I inhibition; zvířata; antibakteriální látky; viabilita buněk; Cell Survival; myši; Intercalation; mikrobiální testy citlivosti; Silver sulfonate; Apoptosis; Animals